Ultra‐Low Threshold Resonance Switching by Terahertz Field Enhancement‐Induced Nanobridge - Sang‐Hun Lee; Moohyuk Kim; Yeeun Roh; Myung‐Ki Kim; Minah Seo (Advanced Science)
Abstract Ongoing efforts spanning decades aim to enhance the efficiency of optical devices, highlighting the need for a pioneering approach in the development of next‐generation components over a broad range of electromagnetic wave spectra. The nonlinear transport of photoexcited carriers in semiconductors at low photon energies is crucial to advancements in semiconductor technology, communication, sensing, and various other fields. In this study, ultra‐low threshold resonance mode switching by strong nonlinear carrier transport beyond the semi‐classical Boltzmann transport regime using terahertz (THz) electromagnetic waves are demonstrated, whose energy is thousands of times smaller than the bandgap. This is achieved by employing elaborately fabricated 3D tip structures at the nanoscale, and nonlinear effects are directly observed with the THz resonance mode switching. The nanotip structure intensively localizes the THz field and amplifies it by more than ten thousand times, leading to the first observation of carrier multiplication phenomena in these low‐intensity THz fields. This experimental findings, confirmed by concrete calculations, shed light on the newly discovered nonlinear behavior of THz fields and their strong interactions with nanoscale structures, with potential implications and insights for advanced THz technologies beyond the quantum regime.